TCR-based cellular immunotherapy for hepatocellular carcinoma: advances, challenges, and prospects - Zeng, Wanting; Zhu, Wei; Yuan, Guosheng; Chen, Jinzhang; Wang, Zhanhui; Hou, Jinlin; Jiang, De-Ke (Cancer Immunology, Immunotherapy : CII, 2025)
Hepatocellular carcinoma (HCC) ranks among the most prevalent malignant tumors globally. However, current frontline treatment modalities fail to achieve satisfactory therapeutic outcomes. In recent years, T-cell receptor (TCR)-T therapy has garnered increasing attention as a promising therapeutic approach. This review provides an overview of the epidemiology of HCC, evaluates the efficacy of current first-line treatment options, and introduces adoptive cellular therapies (ACTs), with a specific focus on TCR-T therapy. Notably, we categorize existing TCR-T research targeting different antigens for the treatment of HCC, covering both published literature and registered clinical trials. Furthermore, we discuss the limitations of current TCR-T research and applications, while offering insights into future research directions and development prospects. In summary, this review comprehensively examines the research progress on TCR-T therapy for HCC from the perspective of antigen targeting. Although several challenges remain to be addressed, we believe that TCR-T therapy represents a promising approach for the treatment of HCC.